Case 3603: Icthyophaga Lesson, 1843 (Aves, Falconiformes, Accipitridae), and Ichthyophaga Syromjatnikova, 1949 (Platyhelminthes, Turbellaria, Urastomidae): proposed conservation of both generic names - Williams, E H Jr; Bunkley-Williams, L (Bulletin of Zoological Nomenclature)
Closed in BZN 74 (31 Aug 2017): 142.